Pollutant Removal from Municipal Sewage by Optimized Anaerobic Pond and Subsurface Flow Wetland - Rahmani Sani, Abolfazl; Mehrdadi, Naser; Azimi, Aliakbar; Delara, Mahin (Asian Journal of Chemistry, 2012)
This research project was initiated to refine the knowledge available on the treatment of municipal wastewater by combined anaerobic ponds and wetlands. To determine the treatment capacity of combined system, a pilot scale of anaerobic ponds and subsurface flow wetland was built and monitored over one treatment year. The anaerobic pond systems consisted of two ponds: a) conventional pond and b) optimized pond that are combined with two wetland cell units respectively. The conventional pond was built in common method and optimized pond in two parts i.e., part one as a digestion pit with 12 h detention time and part two as an anaerobic baffled pond with 8 across baffles and 36 h detention time. The experiments were started with a tracer study to find out the hydraulic characteristics of each pond. Two subsurface flow wetlands with a two day hydraulic detention time and bulrush plant were built. Water samples at the inlet and outlet of each component of the combined system were analyzed biweekly for biochemical oxygen demand (BOD5), total suspended solid (TSS), total kjeldalh nitrogen (TKN), total phosphorus (TP) and total coliform (TC). The average removal efficiency of conventional and optimized ponds combined with wetland cells were as follows: BOD5 (68.5 %-88 %), TSS (82.6 %-96.3 %), TKN (83 %-93.2 %), TP (83 %-91 %) and TC (94 %-98 %) respectively.